Case Report: A Child with Gross Hematuria and the Importance of Travel History - Shatat, Ibrahim F. (Frontiers in Pediatrics, 2018)
We report a case of a 5 year-old young girl known to have vitiligo who presented with a 3 month-long history of gross hematuria. She underwent an extensive laboratory workup and a kidney biopsy, all of which were within normal limits. While being prepared for a cystoscopy and more advanced imaging of the urinary tract, the family mentioned history of travel to a schistosomiasis endemic area prompting a more thorough ova and parasite examination of the urine. Urine microscopy confirmed the diagnosis of Schistosoma hematobium.